Unilateral absence of musculocutaneus nerve and its clinical significance - Rohilla, Aarti; Rohilla, Jyoti; Singh, Kamal; Rathee, Suresh Kanta (International Journal of Research in Medical Sciences, 2017)
Musculocutaneous nerve arises from lateral cord and supplies the muscles of front of arm and then continues as lateral cutaneous nerve of forearm. Musculocutaneous nerve has frequent variations. Nerve may be doubled or even absent. There is unilateral absence of musculocutaneous nerve in this case. Musculocutaneous nerve arises from lateral cord and supplies the muscles of front of arm and then continues as lateral cutaneous nerve of forearm. Musculocutaneous nerve has frequent variations. Nerve may be doubled or even absent. There is unilateral absence of musculocutaneous nerve in this case. Musculocutaneous nerve was seen to be absent in one case on right side. Branches arise either from lateral cord or median nerve to supply the flexor muscles of arm. Total absent musculocutaneous nerve is quiet uncommon. Hence knowledge of this variation can help clinicians in understanding the cause of weakness or paralysis of flexor muscles of arm due to median nerve injury which is unusual.